Handling Organized Land Crimes through Collaborative Governance In Central Kalimantan Province - Ismawanto, Chandra; Panggabean, Mompang; Tehupeiory, Aertje (LEGAL BRIEF, 2026)
Research This leave from increasing case action criminal land that is carried out in a way organized or known with the term land mafia , which gives rise to inequality agrarian and weakening trust public to system law . Problems main thing studied is How effectiveness approach collaborative between institution in handling action criminal land in Central Kalimantan Province through the Integrated Team Prevention and Eradication of Land Mafia. Research This use approach juridical empirical (socio-legal research) with characteristic descriptive-analytical , through collection of primary data and secondary data ( regulations legislation , documents official , and literature law ). Research results show that approach collaborative between the Ministry of ATR/BPN, the Prosecutor's Office , the Police , and the Regional Government has strengthen coordination in pre-vention and enforcement law case land , although Still there is constraint in the form of limitations authority , overlapping overlap regulations , and not yet optimally digitization of land data . Therefore that , is necessary formation regulations special about action criminal land , strengthening institutional Task Force become permanent , and integration digital- based data system for realize enforcement effective , transparent and just law agrarian